2021
DOI: 10.1001/jamaoncol.2021.2301
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Plus Concurrent Chemoradiation Therapy in Patients With Unresectable, Locally Advanced, Stage III Non–Small Cell Lung Cancer

Abstract: plus concurrent chemoradiation therapy (cCRT) may provide treatment benefit to patients with locally advanced, stage III non-small cell lung cancer (NSCLC).OBJECTIVE To evaluate treatment outcomes and safety of pembrolizumab plus cCRT in stage III NSCLC. DESIGN, SETTING, AND PARTICIPANTSThe phase 2, nonrandomized, 2-cohort, open-label KEYNOTE-799 study enrolled patients between November 5, 2018, and July 31, 2020, from 52 academic facilities and community-based institutions across 10 countries. As of October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(117 citation statements)
references
References 37 publications
3
113
1
Order By: Relevance
“…First, patients herein received full courses of ICIs prior to RT initiation, whereas in other studies ( 11 16 ) most patients did not have as high of a degree of immune system galvanization prior to commencing RT. KEYNOTE-799 (which delivered ICIs before RT) observed a <10% rate of grade ≥3 pneumonitis, but that trial delivered a median of 1 cycle of pembrolizumab/chemotherapy prior to RT (as compared to a median of 4 cycles herein) ( 18 ). The higher level of immune activation prior to starting RT in this cohort could have predisposed these patients to develop RP more frequently and with greater severity than patients in the aforementioned publications, but this notion requires further corroboration.…”
Section: Discussionmentioning
confidence: 99%
“…First, patients herein received full courses of ICIs prior to RT initiation, whereas in other studies ( 11 16 ) most patients did not have as high of a degree of immune system galvanization prior to commencing RT. KEYNOTE-799 (which delivered ICIs before RT) observed a <10% rate of grade ≥3 pneumonitis, but that trial delivered a median of 1 cycle of pembrolizumab/chemotherapy prior to RT (as compared to a median of 4 cycles herein) ( 18 ). The higher level of immune activation prior to starting RT in this cohort could have predisposed these patients to develop RP more frequently and with greater severity than patients in the aforementioned publications, but this notion requires further corroboration.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the FDA approval of atezolizumab as the adjuvant therapy for this patient population. Similarly, in the phase 2 KEYNOTE-799 trial, pembrolizumab plus concurrent chemoradiation therapy demonstrated objective response rates of 71% in locally advanced, stage III NSCLC ( Jabbour et al, 2021 ). Because our case was a locally advanced dMMR/MSI-H tumor, we were also interested in the efficacy of adjuvant immunotherapy in this setting.…”
Section: Discussionmentioning
confidence: 98%
“…Van den Ende et al showed the feasibility of concurrent ICI use with CRT in a neoadjuvant setting before resectioning of esophageal carcinoma [ 44 ]. Furthermore, a recent nonrandomized phase II trial of pembrolizumab concurrent to CRT in patients with locally advanced stage III NSCLC demonstrated objective response rates of 70% [ 45 ]. Although toxicity in this regime was relatively high, with 58% of patients experiencing any grade 3–5 AEs leading to treatment discontinuation in 26%, this seems acceptable considering the historical response rates of CRT between 35.9 and 54.5% [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%